[Рассказы, юморески]. 1885 - 1886 - Чехов Антон Павлович (2007)
Экземпляры: до аб (20160126) / Инвентарный номер: 191440 / Цена: / Сис.шифр: 84 / Авт.знак: Ч-56 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)5-445